Optimalisasi Intervensi pada Peran Guru dalam Pendidikan Inklusi: Sebuah Systematic Literature Review Berbasis Index for Inclusion - Hardiani, Alifa Fauziah; Hendriani, Wiwin (Nusantara: Jurnal Pendidikan Indonesia, 2025)
Purpose – This study aims to explore interventions implemented to optimize the role of teachers in inclusive education through a systematic literature review.Method – This study adopts a Systematic Literature Review (SLR) guided by PRISMA and structured using the PICO framework. From an initial pool of 63 articles, 13 were selected through a multistage screening process. Data were analyzed using a narrative synthesis approach, based on the Index for Inclusion framework (Booth & Ainscow, 2002), encompassing the dimensions of culture, policy, and practice in inclusive education. Findings – The review reveals that most interventions focused on teacher training—both theoretical and practical—to enhance pedagogical competence and responsiveness to student diversity. Several studies also emphasized the importance of inclusive values, attitudes, and stakeholder collaboration. The practice dimension appeared in 85% of articles, culture in 92%, and policy in 54%. These findings underscore the need for a systemic approach to inclusive education that integrates instructional strategies, supportive policies, and an inclusive school culture. Research Implications – This study highlights the need for teacher development programs that integrate policy frameworks, technical training which includes psychosocial approaches, and inclusive school culture in a cohesive manner. It also underscores the importance of long-term evaluation and structural reforms to sustain inclusive practices, especially in developing countries.